2005
DOI: 10.1159/000082415
|View full text |Cite
|
Sign up to set email alerts
|

Wheat cytogenetics in the genomics era and its relevance to breeding

Abstract: Hexaploid wheat is a species that has been subjected to most extensive cytogenetic studies. This has contributed to understanding the mechanism of the evolution of polyploids involving diploidization through genetic restriction of chromosome pairing to only homologous chromosomes. The availability of a variety of aneuploids and the ph mutants (Ph1 and Ph2) in bread wheat also allowed chromosome manipulations leading to the development of alien addition/substitution lines and the introgression of alien chromoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 269 publications
0
18
0
1
Order By: Relevance
“…For this purpose, a large variety of wild and cultivated wheat relatives, e.g. rye, Triticum spp., Aegilops spp., Thinopyron spp., have been employed in alien introgression programs (14,19,25,30,33,37,59).…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose, a large variety of wild and cultivated wheat relatives, e.g. rye, Triticum spp., Aegilops spp., Thinopyron spp., have been employed in alien introgression programs (14,19,25,30,33,37,59).…”
Section: Resultsmentioning
confidence: 99%
“…A variety of molecular markers including RFLPs, SSRs and AFLPs have been developed and used in this crop for different purposes including the construction of molecular maps (Somers et al 2004;Goyal et al 2005;Liu et al 2005;Song et al 2005). More recently, EST database has also been utilized in this crop for development of a variety of functional markers, particularly the EST-SSRs (Gupta & Rustgi 2004;Gupta et al 2005). An extensive study for assigning > 16 000 EST loci to chromosome bins has also been completed recently (Qi et al 2004;Peng & Lapitan 2005), although these mapped ESTs cannot be directly used as markers.…”
mentioning
confidence: 99%
“…An extensive study for assigning > 16 000 EST loci to chromosome bins has also been completed recently (Qi et al 2004;Peng & Lapitan 2005), although these mapped ESTs cannot be directly used as markers. However, taken together, only ~7000 molecular markers have so far been placed on different maps (Somers et al 2004;Gupta et al 2005;Liu et al 2005;Song et al 2005;Sourdille et al 2005) although according to some estimates, as many as 10 000 to 20 000 markers are needed on one map to have a reasonably high-density map in bread wheat (Appels 2003). Therefore, keeping in view the need for developing and mapping additional markers, emphasis is now shifting to a new class of abundant markers, the single nucleotide polymorphisms (SNPs).…”
mentioning
confidence: 99%
“…Development of these resources for discovery of molecular markers was a priority in the wake of the genomics era and several projects were undertaken to build them up including the sequencing of FOSMID libraries, whole genome shotgun sequencing (Brenchley et al, 2012), sequencing of expressed sequence tags (ESTs) and the construction and sequencing of bacterial artificial chromosomes (BAC) libraries (Allouis et al, 2003(Allouis et al, , Šafář et al, 2010(Allouis et al, , Šafář et al, 2004. These new resources coupled with the extensive cytogenetic resources that have been developed since the beginning of the 20 th century have been used to improve our knowledge of the genomic architecture of wheat (Gupta et al, 2005, McFadden and Sears, 1946, Kihara, 1919, Sakamura, 1918. The ultimate goal was the construction of the complete physical map of hexaploid wheat.…”
Section: Wheat Breedingmentioning
confidence: 99%
“…Genetic mapping assays have shown that the D genome consistently has fewer markers and recombination bins , Li et al, 2015c, Sorrells et al, 2011, Semagn et al, 2006, Gupta et al, 2005, KamMorgan, 1988. It has been suggested that the little diversity found in the D genome is due to the little gene flow between the wild relative Ae.…”
Section: Wheat Genetics and Genomicsmentioning
confidence: 99%